2014
DOI: 10.1159/000358712
|View full text |Cite
|
Sign up to set email alerts
|

14-Thienyl Methylene Matrine (YYJ18), the Derivative from Matrine, Induces Apoptosis of Human Nasopharyngeal Carcinoma Cells by Targeting MAPK and PI3K/Akt Pathways <b><i>in Vitro</i></b>

Abstract: Background/Aims: Nasopharyngeal carcinoma (NPC) is a distinctive type of head and neck cancer with the highest incidence in South China. Previous studies have proved that matrine, a main alkaloid isolated from Sophora flavescens Ait, has antitumor activity against NPC. However, the effect is not so pronounced and the underlying mechanism remains largely unclear. Here we investigated whether 14-thienyl methylene matrine (YYJ18) that was derived from matrine could exert more effective suppression activity on NPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In mammalian sperm, these proteins act as regulators of sperm motility and the acrosome reaction [33]. Several previous reports have shown that matrine can inactivate ERK1/2 in various cancer cells in vitro [9,11,38]. In this study, we found that matrine also inactivates ERK1/2 signaling by suppressing the phosphorylation of ERK1/2 in mouse sperm (Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In mammalian sperm, these proteins act as regulators of sperm motility and the acrosome reaction [33]. Several previous reports have shown that matrine can inactivate ERK1/2 in various cancer cells in vitro [9,11,38]. In this study, we found that matrine also inactivates ERK1/2 signaling by suppressing the phosphorylation of ERK1/2 in mouse sperm (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…An intensive investigation into the pharmacology and clinical applications of matrine has been ongoing in China for the past decade [2,3,4,5,6]. Matrine has been widely used for the treatment of chronic hepatitis B and chronic hepatitis C since 1998 and has recently been reported to have anti-tumor activities with potential as an adjunct therapy for cancers [5,7,8,9,10,11]. Based on its effects on potassium and calcium currents as well as intracellular calcium concentration ([Ca 2+ ] i ) in rat ventricular myocytes and mouse atrial cardiomyocytes, matrine has also been used for the treatment of heart arrhythmias [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Because apoptosis induction appears to be the most important property for candidate anticancer drug, the morphological observation was conducted to explore whether the cytotoxic effect was related with the apoptotic process [4][5][6]. Elevation of oxidative stress species (ROS) in excess of the buffering capacity designed to modulate ROS levels result in potentially cytotoxic effect [7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NPC is low in most parts of the world, whereas it is high in southern China and other Southeast Asian Qi et [2]. Despite significant advancements in the treatment of NPC, the average 5-year survival rate remains between 34% and 52% [3].…”
Section: Introductionmentioning
confidence: 99%